The expression of autophagy-related gene CXCL12 in endometriosis associated ovarian cancer and pan-cancer analysis - Yuan, Mingwei; Chen, Sijing; Liao, Zelan; Wang, Kana (Frontiers in Endocrinology, 2025)
BackgroundEndometriosis-associated ovarian cancer (EAOC), an aggressive form of malignant ovarian neoplasm with origins in endometriosis (EM), has risen to prominence recently. Despite extensive investigation, the precise pathophysiology remains elusive.This article explores new autophagy-related DEG genes between EM and EAOC, and investigates CXCL12’s expression and prognostic relevance across pan-cancer.MethodsFrom Gene Expression Omnibus (GEO), we retrieved gene sequencing data to uncover DEGs. We carried out enrichment analysis, PPI network construction and explored CXCL12’s multi-database expression and prognostic significance employing the analytical tools of ONCOMINE, PrognoScan, GEPIA, and Kaplan-Meier Plotter. Subsequently, assessing the relationship between CXCL12 expression and immune presence in cancer utilizing GEPIA and TIMER. Lastly, CXCL12, IL17, STAT3, and FOXP3 protein expressions were determined through immunohistochemistry analysis in EAOC, EM, and normal endometrial tissues.ResultsTwo DEGs were discovered and enrichment analysis indicated virus-cytokine/receptor interactions, chemokine signaling, and cytokine-cytokine receptor interplay as pivotal in EAOC. Notably, cancerous tissues exhibited reduced CXCL12 levels compared with non-malignant tissues across cancers. CXCL12, IL17, STAT3, Th17/Treg ratio, and FOXP3 expressions were also lower in EAOC than EM and normal tissues. Additionally, CXCL12 expression was related to stage, survival, immune subtype, and molecular classification across cancers.ConclusionsIn conclusion, our study implicates CXCL12 and altered Th17/Treg balance in progression from EM to EAOC. CXCL12 emerges as a predictive marker for cancer progression across various tumors and is associated with inflammatory response.